THE IDEOLOGICAL SIGNIFICANCE OF PROTECTING HUMAN INTERESTS - Olimova Mukhtasar Rayimovna (Galaxy International Interdisciplinary Research Journal, 2024)
This scientific article talks about the important ideological aspects of prioritizing and protecting human interests. Analyzing the moral, social and philosophical aspects of this imperative, the article aims to emphasize the fundamental importance of protecting human interests in the development of a fair, just and sustainable society. Based on interdisciplinary perspectives, the article examines how protection of human interests serves as a basis for ethical decision-making, social development, and preservation of human dignity.